Le fonds d’œuvres d’art de la Casa de Velázquez. Constitution et perspectives - Charlotte Krzyzanski (Mélanges de la Casa de Velázquez, 2025)
Since its creation, Casa de Velázquez has housed a varied collection of works of art, built up through successive donations from artists in residence. This collection, which reflects the evolution of both the institution and artistic practices, now forms a large and heterogeneous body of work. As it approaches its centenary in 2028, Casa de Velázquez is taking a closer look at its history and development, and at the challenges it faces in terms of enhancing its value and future direction.